2011
DOI: 10.1186/1757-2215-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Metformin therapy in a hyperandrogenic anovulatory mutant murine model with polycystic ovarian syndrome characteristics improves oocyte maturity during superovulation

Abstract: BackgroundMetformin, an oral biguanide traditionally used for the treatment of type 2 diabetes, is widely used for the management of polycystic ovary syndrome (PCOS)-related anovulation. Because of the significant prevalence of insulin resistance and glucose intolerance in PCOS patients, and their putative role in ovulatory dysfunction, the use of metformin was touted as a means to improve ovulatory function and reproductive outcomes in PCOS patients. To date, there has been inconsistent evidence to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The disrupted hypothalamic-pituitary synchrony, increased gonadotropin pulsatile secretion, destroyed oocyte-granulosa cell interaction, increased ovarian androgen production, hyperinsulinemia, and insulin resistance included the etiologies of PCOS [13]. Studies confirmed that the DHEA-treated PCOS murine model exhibits many of the salient features of human PCOS [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The disrupted hypothalamic-pituitary synchrony, increased gonadotropin pulsatile secretion, destroyed oocyte-granulosa cell interaction, increased ovarian androgen production, hyperinsulinemia, and insulin resistance included the etiologies of PCOS [13]. Studies confirmed that the DHEA-treated PCOS murine model exhibits many of the salient features of human PCOS [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Adult ob/ob and db/db females are infertile and exhibited acyclicity, anovulation, and increased follicular atresia [89][90][91][92]. Hormone changes in ob/ob mice included significantly increased serum T, E2, and P levels [93,94] and reduced serum FSH levels [95], while db/db females exhibited a significant decrease in serum E2 and P levels. Metabolic features of PCOS exhibited by both mutant mice include severe obesity, a diabetes-like syndrome of hyperglycemia, glucose intolerance, and elevated plasma insulin [91,94,[96][97][98].…”
Section: Leptin Mutant Rodent Strainsmentioning
confidence: 99%
“…Hormone changes in ob/ob mice included significantly increased serum T, E2, and P levels [93,94] and reduced serum FSH levels [95], while db/db females exhibited a significant decrease in serum E2 and P levels. Metabolic features of PCOS exhibited by both mutant mice include severe obesity, a diabetes-like syndrome of hyperglycemia, glucose intolerance, and elevated plasma insulin [91,94,[96][97][98]. However unlike human PCOS, polycystic ovaries were not present in either model, and serum LH levels were unchanged in ob/ob mice [95].…”
Section: Leptin Mutant Rodent Strainsmentioning
confidence: 99%
“…13 AMPK is a multi-substrate enzyme that is activated in response to physiological and pharmacological stimuli, which have important roles not only in metabolism but also in reproduction and, more precisely, in the ovary. 14,19 Metformin, as an insulin sensitizer drug, could decrease estradiol and progesterone secretion through an AMPK-dependent mechanism in bovine granulosa cells. 15 The upstream kinases of AMPK, LKB1, and calcium/calmodulin-dependent protein kinase kinase-β (CaMKKβ) activate it by phosphorylating Thr172 in the activation loop of the catalytic α-subunit.…”
Section: Introductionmentioning
confidence: 99%
“…18 It has been shown that Aicar, an activator of AMPK, could reduce progesterone secretion by decreasing 3β-HSD production in rat granulosa cells. 14,19 Metformin, as an insulin sensitizer drug, could decrease estradiol and progesterone secretion through an AMPK-dependent mechanism in bovine granulosa cells. 18 Considering the role of AMPK in energy homeostasis and its possible role in ovarian function, some studies have declared, it may be involved in the interactions between metabolism and reproduction.…”
Section: Introductionmentioning
confidence: 99%